The Impact of Selective Dry Cow Therapy Adopted in a Brazilian Farm on Bacterial Diversity and the Abundance of Quarter Milk - Goncalves, Juliano L.; Young, Juliana; Leite, Renata de F.; Fidelis, Carlos E.; Trevisoli, Priscila A.; Coutinho, Luiz L.; Silva, Nathália C. C.; Cue, Roger I.; Rall, Vera Lucia Mores [UNESP]; dos Santos, Marcos V. (MDPI, 2022)
We aimed to evaluate the impact of selective dry cow therapy (SDCT) (protocol 1: antimicrobial combined with internal teat sealant (ITS); vs. protocol 2: ITS alone) on bacterial diversity and the abundance of quarter milk. Eighty high production cows (parity ≤ 3 and an average milk yield of 36.5 kg/cow/day) from the largest Brazilian dairy herd available were randomly selected; milk quarter samples were collected for microbiological culture (MC) on the day of drying-off (n = 313) and on day 7 post-calving (n = 313). Based on the results of the MC before and after calving, 240 quarters out of 313 were considered healthy, 38 were cured, 29 showed new infections and 6 had persistent infections. Mammary quarters were randomly selected based on intramammary information status and SDCT protocols for bacterial diversity analyses. The bacterial diversity was similar when comparing both healthy and cured quarters submitted to both drying-off protocols. Despite healthy cows that were treated at dry-off using only teat sealant showing no alteration in the alpha and beta bacterial diversity, they did show a higher abundance of bacterial groups that may be beneficial to or commensals of the mammary gland, which implies that antibiotic therapy should be reserved for mammary quarters with a history of mastitis.
Keywords: antibiotic resistance; bacterial diversity; internal teat sealant; new intramammary infection; selective dry cow therapy